Peningkatan Kompetensi Aparatur Desa dalam Meningkatkan Kepuasan Masyarakat terhadap Pelayanan Administrasi di Desa Kundi : Studi Khasus Desa Kundi, Kecamatan Simpang Teritip, Kabupaten Bangka Barat, Provensi Kepulauan Bangka Belitung - Soromiani Soromiani; Yayat Sujatna; Ambardi Ambardi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the Increase in Village Apparatus Capacity on the Level of Community Satisfaction with Administrative Services in Kundi Village (Special Study of Kundi Village, Simpang Teritip District, West Bangka Regency, Bangka Belitung Islands Province). The purpose of this study was to determine the increase in the capacity of village heads and Village Apparatus on the Level of Community Satisfaction with Administrative Services in Kundi Village, Simpang Teritip District, West Bangka Regency, Bangka Belitung Islands Province. The capacity of the Village Head and Village Apparatus of Kundi is seen from three indicators, namely, skills, abilities and quality of human resources. The research used a qualitative approach. The research informants numbered 11 people with 1 person as a key informant. Data collection techniques used interview techniques (based on interview guidelines), observation and documentation. Furthermore, data analysis was carried out qualitatively. The results of the study on the skill indicator, the Kundi Village Apparatus has carried out its duties and functions skillfully. On the ability indicator, the Kundi Village Apparatus has been able to manage data well and in accordance with the rules with community expectations. In the human resource quality indicator, the Kundi Village Apparatus has been able to describe the level of community welfare. This shows that there is an increase in the capacity of the Kundi Village apparatus compared to the previous year. The Kundi Village Apparatus has been equipped with training and education that supports the increase in capacity.